A Comparative Study of Colour Metaphors in English and Arabic: Implications for Second Language Acquisition and Translation - Ibrahim, Mahmoud Mohamed ElMahdi (2017)
The aim of this descriptive comparison study is to analyze the colour metaphorical terms used in both English and Arabic. This study ponders upon the process of construing colours across cultures, specifically English and Arabic culture. The researcher chooses the six basic colours (white, black, red, green, yellow, and blue) to uncover the conceptual meaning underpinning the interaction between culture and language. The researcher approaches the colour terms in Arabic and English without any preconceived data. Additionally, the researcher investigates the ‘X-phemisms’ connotation of the six basic colour terms in both languages since the colour system of both is not identical. The results of this investigation helps the researcher to identify the most frequent type of ‘X-phemisms’ in Arabic and English. The researcher identified three different meanings for each colour term according to the cognitive cultural categorization (Xing, 2009). The basic meaning, the extended meaning and the additional/abstract meaning. The results of this comparative study indicates that although the basic meaning of colours are overlapping in English and Arabic, but most of the extended meaning of colours are culture-specific. Those results also confirms the belief that our understanding includes metaphorical forms which combine all of the influences (historical, cultural, linguistic, bodily, perceptual and economic). Those multi-facet influences construct the fabric of human meaningful experiences. The pedagogical aim of this study is to move the language learners and translators up to a higher level where they can be fully fluent and culturally aware of their target language. This study has two-fold significance. The first is to enhance knowledge of universals, variations and historical development in the field of colour terminology. In addition, it contributes to the current knowledge in the field of cross-cultural studies on language and culture, especially with regard to idiomatic expressions. The second is to give a vivid descriptive and comparative analysis of colour metaphors in both English and Arabic. It also investigates the idea of how colour metaphors are interrelated to languages, cultures and cognition.